EFFECT OF GREEN PRODUCT KNOWLEDGE AND PERCEPTION ON GREEN PURCHASE INTENTION; MODERATING ROLE OF PRICE CONSCIOUSNESS - Faisal, Malik Muhammad; Hafeez, Muhammad; Hafeez, Muhammad; Zia, Mubashar Hassan; Haider, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Green products are rapidly moving from niche markets to large market segments and the number of consumers purchasing green products is rapidly penetrating mainstream markets (Roberts, 1996). As the majority of the consumers are concerned about the environment, green markets are developing rapidly and quickly (Peateie and Crane, 2005). These green markets have created the essence of doing green marketing. Price is one of such factors that may prevent a green consumer to buy an eco-friendly product (Bonini and Oppenheim, 2008). Tanner et al., 2003 also confirms this relationship between buying intentions of consumers and the price of green products. Similarly, environmental awareness in the midst of customers is growing making them more worried about green and buying of foodstuff. By analyzing this by using the theory of reasoned actions, green purchase intentions are affected differently by different and type of prices. Data gathered from 400 customers while structured questionnaires were used to gather primary data from consumers. For hypothesis, testing process macro was used. CFA was run by using AMOS. There have been discussed results along with recommendations and future directions at the end.